The Role of Jurisprudence in Activating the Rules of Justice as a Source of Civil Law - Zayer, Sattar Jabbar (TRUNOJOYO LAW REVIEW, 2025)
This article examines the concept of the rules of justice and their application within the Iraqi legal system, conducting a comparative analysis of other legal frameworks. The study utilizes doctrinal legal research to explore this issue based on primary and secondary sources, albeit with case laws of the Iraqi courts serving to occupy the research samples from which we have been inspired to ascertain the image of justice rules in the Iraqi milieu and the degree of commitment in assimilating the epistemology of justice in comparative legal systems. Judiciary can make law more realistic and living, its conclusions are further called for high-level ability of diligence, logic and facts-based induction to create a solution based upon the rules of justice in the realm of judicial jurisprudence, which operates in the current legal regime. Ultimately, this study provides crucial lessons regarding the changing cardiopulmonary role of the rules of justice through varying legal traditions and highlights the indispensable nature of judicial jurisprudence in upholding the principles of equality and justice.